Seropositivity of Visceral leishmaniasis on people of VL endemic three districts of Nepal. (February 2021) - Basnyat, Shaila; Banjara, Megha Raj; Ghimire, Prakash; Matlashewski, Greg; Singh, Anjana
Abstract: Visceral leishmaniasis (VL) is a life-threatening vector borne disease caused by the Leishmania donovani species complex. In Nepal, it is transmitted to humans by L donovani infected Phlebotomus argentipes sand flies [12 ]. The pathogenesis of VL is complex, and the clinical presentation ranges from asymptomatic infection to severe and fatal disease. Asymptomatic infection may act as potential reservoirs for sustained transmission of VL in endemic areas. We investigated the sero-prevalence of symptomatic and asymptomatic infection of VL in people of three endemic districts of Nepal by serology targeting family members and neighbors of VL patients. Sero-survey was conducted among 189 people of villages endemic to VL from Palpa, Sarlahi and Saptari districts during 2016 to 2018 using the rK39 rapid diagnostic test (InBios International, Seattle, WA) to detect anti- Leishmania antibodies. Sero-positivity was 35.7% (10/28) in people tested from Sarlahi districts, 6% (3/50) in Saptari district and 1.7% (1/59) from the Palpa district. In Sarlahi, sero-positivity was found to be highest among the age group below 15 years (44.5%). All family members of diagnosed VL cases in Saptari and Palpa districts were found to be rK39 test negative. In Sarlahi district, among the ten sero-positive cases, nine were febrile and became symptomatic VL cases after few days and one case remained asymptomatic during the six month follow up. Asymptomatic cases in VL endemic districts of Nepal were found to be sero-positive, screening of people in VL endemic districts would be important for prevention of VL transmission. Highlights: A Sero-survey was conducted among 189 people from four villages from three VL endemic districts of Nepal.In the village of Ishworpur located in the Sarlahidistrict, there was a high level ofsero-positivity (10/28). These 10 seropositive cases were from 6 house holds out of total 11 households of Sarlahi districts. In Belichapena of Saptari district, the level of rK39 positive individuals was also relatively high(3/50). In two separate Rampur and Pipaldanda villages of the Palpa district, 2/111 tests were positive on the rK39 RDT. It was interesting to identify one village Ishworpur in the Sarlahi where 10 out of 28 people tested were positive when the rK39 tests were performed in the laboratory. Out of these 10, 9 developed VL within 15 days of the tests being performed. The high level of rK39-positive individuals in Ishworpur revealed a very high level of transmission in this village. This is a village living in low socioeconomic conditions(Data not shown). In Ishworpur village of Sarlahi district, 4 seropositive cases were from different households, 3 seropositve caseswere from same household and the other 3 seropositive case were also from another same household. In the Palpa district, among 111samples tested, one each in Rampur and Pipaldanda was found to be sero-positive. All family members of diagnosed VL cases in two villages of Palpa district were found to be sero-negative. In Belichapena, VDC of the Saptari district, all 3 seropositive cases were from three individual households. Overall, this indicates there is no clustered outbreak in Palpa and Saptari districts as was the case in Ishworpur in the Sarlahi district.